Accounting Design Project to Improve the Quality of Financial Statement Information - Endah Susilowati; Diah Hari Suryaningrum; Sari Andayani; Arie Kusuma Dewa; Salsabilla Narita Kusnadi; Gading Tio Yuniar; Khansa Hasna Nur Khairunnisa; Firzano Triardanaputra Silalahi; Nuril Ade Pramudita; Henoch Setyo Purnomo (Nusantara Science and Technology Proceedings, 2022)
"Ning Har Sambel Pecel Suroboyo" is an MSME company that produces chili sauce. To date, the company has not had financial reports that can provide information about business performance. Therefore, the purpose of the Community Service Program for the Utilization of Science and Technology for the Community (PIKAT) is to provide training and assistance to MSME owners "Ning Har Sambel Pecel Suroboyo", in their financial records. The financial records carried out by Ning Har SMEs are very simple and are recorded manually. Records only consist of cash receipts and disbursements. With the development of Ning Har businesses, Ning Har needs better records and financial statements to assess its financial performance. Through this PIKAT program, the owner was assisted and trained in operating simple computerized financial reports, named Count and Grow. The Count and Grow Excel application was created based on the results of interviews and identification of Ning Har's business transactions. In addition, Count and Grow is also adjusted to financial accounting standards for MSMEs. Thus, the Count and Grow application will be able to increase the accounting knowledge of Ning Har's business owners, provide performance information, and facilitate business financial planning and management as well as manage business cash flows. With the increasing quality of financial performance reporting and cash flow, the of business turnover will increase and Ning Har Sambel Pecel's MSME business will develop more rapidly.